2022
DOI: 10.3389/fmed.2022.935424
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal cardiopulmonary resuscitation in adults and children: A review of literature, published guidelines and pediatric single-center program building experience

Abstract: Extracorporeal cardiopulmonary resuscitation (ECPR) is an adjunct supportive therapy to conventional cardiopulmonary resuscitation (CCPR) employing veno-arterial extracorporeal membrane oxygenation (VA-ECMO) in the setting of refractory cardiac arrest. Its use has seen a significant increase in the past decade, providing hope for good functional recovery to patients with cardiac arrest refractory to conventional resuscitation maneuvers. This review paper aims to summarize key findings from the ECPR literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 212 publications
0
2
0
Order By: Relevance
“…Multiple studies in adults have demonstrated improved survival with ECPR compared to conventional CPR, considering survival to discharge and neurological impairment outcomes [3]. These findings have also been demonstrated in a recent systemic review and meta-analysis that reported 30% survival with favorable neurological outcomes [8]. These results seem to indicate that ECPR may play a favorable role in improving pediatric cardiac arrest outcomes.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Multiple studies in adults have demonstrated improved survival with ECPR compared to conventional CPR, considering survival to discharge and neurological impairment outcomes [3]. These findings have also been demonstrated in a recent systemic review and meta-analysis that reported 30% survival with favorable neurological outcomes [8]. These results seem to indicate that ECPR may play a favorable role in improving pediatric cardiac arrest outcomes.…”
Section: Discussionmentioning
confidence: 75%
“…This efficient approach was mainly due to the clinical field where the cardiac arrest occurs -the operative room. In this specific scenario, continuous monitoring allows prompt detection and immediate assistance reducing the no-flow time [8].…”
Section: Conclusion Additional Information Author Contributionsmentioning
confidence: 99%
“…54 In the future, carefully selected randomised-controlled trials are necessary to aid in patient selection, pre-ECPR practice, and post-ECPR practice. 97 The use of artificial intelligence to predict cardiac arrest in children has been studied and seems promising. 98,99 Further research and development is needed to deploy these algorithms in daily practice.…”
Section: Future Directionsmentioning
confidence: 99%
“…Despite advances in resuscitation science and ECMO technology, there remain questions about how to deliver extracorporeal CPR (ECPR) to optimize survival and neurologic outcomes (2–7). The use of ECPR has become increasingly common as outcomes improve in comparison to conventional CPR and variability in its delivery is emerging (5, 8–11).…”
mentioning
confidence: 99%